Proyeksi Kernel GCM pada Sembarang Fungsi - Rizal Kurniadi; Marsongkohadi Marsongkohadi; Zaki Su’ud; Triyanta Triyanta (Institut Teknologi Bandung, 2003)
The GCM kernel projection on arbitrary function is a technique to solve Schredinger integro-differential equation. The Basic idea is making eigen value equation from Schroedinger equation by projecting the GCM kernel into no orthonormal functions. In this paper the technique is presented to calculate ground state energy of deuteron.